Sexual behaviour and negotiation of the male condom by female students of the University of Ibadan, Nigeria (2000)
This study explored the sexual behaviour of unmarried female students of the University of Ibadan, Nigeria, and assessed the extent to which those who were sexually active negotiated and used the male condom. Four focus group discussions were conducted followed by a survey of 354 students. The results show that the mean age of the students was 22.5 years 55.1% had had sexual intercourse; the mean age at first intercourse was 16.5 years. The number of lifetime sexual partners ranged from I to 20 with a mean of 3.4; 75% of those who had had sex reported ever using condom; 16.9% and 39% used it during their first and last sexual episodes respectively; only 34.3% used it consistently. Seventy-three per cent had ever negotiated condom use with a partner, but only 41% did so during their last sexual encounter. A significant association was found between condom negotiation and number of sexual partners: Students with fewer life time partners (3-2) had less frequently negotiated condom use than those with more partners (4.3) (P<0.05). Condom negotiators also scored significantly higher (4.6) on a 6-point AIDS Knowledge Score than those who had never done so (4.0) (P<0.05). About a quarter (26.7%) had ever bought a condom, while 38.5% had ever carried it. We conclude that although many female students had sometimes used a condom, only a few used it consistently and are therefore at risk of unintended outcomes of unprotected sex. We propose appropriate interventions to address the problem .